Analysis of Human Development Indicators in Maysan Governorate - Oleiwi Shami Al Saidi, Hayder; Radees Abd, Naji (International Journal of Psychosocial Rehabilitation, 2020)
This research is concerned about clarifying the reality of human development in Maysan Governorate, by addressing the concept of human development and its most important measures, as well as highlighting the reality of health, education and the standard of living, as the research found that Maysan governorate suffers from a high disadvantage, in addition to the deterioration of the levels of health, education, and living, despite its contribution in producing oil, this decline is due to the decrease in allocations, as well as to the high level of administrative and financial corruption in implementing projects.